Distribution of Lignin, Hemicellulose, and Arabinogalactan Protein in Hemp Phloem Fibers. (3rd September 2018) - Kiyoto, Shingo; Yoshinaga, Arata; Fernandez-Tendero, Eva; Day, Arnaud; Chabbert, Brigitte; Takabe, Keiji
Abstract: The distribution of lignin, 8-5′ and 8-8′ linked lignin substructure, and noncellulosic polysaccharides in hemp ( Cannabis sativa L.) phloem fibers were explored based on histochemical and immunological methods. Ultraviolet absorption and potassium permanganate staining were observed mainly in the compound middle lamella (CML) and S1 layers, and rarely in the G-layer of phloem fibers, suggesting that lignin concentration is high at the CML and S1 layers, and very low at the G-layer of hemp fibers. Acriflavine staining, uniform KM1 labeling (8-5′ linked lignin substructure), and no KM2 labeling (8-8′ linked structure) were observed in the G-layer, suggesting that there is a small amount of lignin-like compound with 8-5′ linked structure in the G-layer. In addition, some fiber cells showed a multilayered structure. Uniform arabinogalactan protein (AGP) labeling was observed on the S1 layers and G-layers using JIM14, but little appeared in the CML of hemp fibers, indicating that these layers of the phloem fibers contain AGP. Immunogold labeling of xylan (LM11) and glucomannan (LM21) showed that xylan and glucomannan were mainly present in the S1 layers and the G-layers, respectively. In some phloem fibers, LM21 immunofluorescence labeling showed multilayered structure, suggesting the heterogeneous distribution of glucomannan.